SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA MENGAJAR GURU - Munawir Izhar; Zakaria Zakaria; Puspa Djuwita (UNIVERSITAS BENGKULU, 2017)
The purpose of this study is to describe the principal academic supervision in increasing teachers teaching performance junior high school 2 Ketahun, including lesson plan, learning prosess,learning evaluation, academic supervision technigue of the principal. This study used deseriptive qualitative method and the technique of data collecting are interview and observation. the subjeet of study are the principal and teacher. The result showed that the teachers have implemented the principal supervision item in increasing teachers teaching performance at junior high school 2 ketahun as the characteristic of the school.